Constitutive Elements of Professional Development Programs for Primary School Mathematics Teachers: Evidence of Proposals from Multiple Countries - Güerci, Victoria; Villella, José (Social Education Research, 2025)
A comparative study is presented, developed with the purpose of identify and characterize proposals for the professional development of mathematics teachers in primary schools around the world from situated approaches, which involve collaborative learning amongst teachers that results in the improvement of their professional practice. The countries whose proposals were analysed are Argentina, Australia, Brazil, Canada, Colombia, Cuba, Spain, France, England, Japan, Mexico, and the Dominican Republic. The conclusions identify and characterize some privileged conditions for designing training processes that contribute to the professional development of mathematics teachers: they must be creative, situated, proactive, collective, based in evidence, and balanced. The professional development of mathematics teachers requires the articulation between two components: an institutional training component and a specific training component subject to a map of vacancies and priorities based on evidence taken from national and international evaluations.